An explorative interview study of men and women on sick leave with a musculoskeletal diagnosis seeking an acceptable life role - Ulla-Britt Eriksson; Staffan Janson (Nordic Journal of Social Research)
Introduction: A dramatic increase in sicknesses absence in Sweden has led to a shift in the public debate. Departing from the view of sickness absence as a result of a poor work environment and stress, the debate in the early 2000s became more concerned with the breakdown of norms and the abuse of sickness insurance. Sickness absence became the responsibility of the individual rather than of society. Aim: This study has sought to explore the consequences of being on sick leave with a musculoskeletal diagnosis, the experiences of encounters with rehabilitation professionals, and the attitudes towards sick-listing from the perspective of the sick-listed persons. Methods: Individual in-depth interviews were conducted in 2010 with eight women and nine men aged 33-60 who were on long-term sick leave (at least 60 days) with a musculoskeletal diagnosis. We analysed the data using a grounded-theory approach. Results: There was an obvious tension between work strategy as a societal norm and finding an acceptable life role when sick-listed. Four groups with partially differing experiences and perceptions crystallized out of the total population. These experiences and perceptions formed their choice of different acceptable life roles and strategies for gaining self-respect and the respect of others. Discussion: The fact that the four groups that emerged from our study experienced their sickness absence in different ways and their pathways back to work were different demonstrates the value of not considering those on sick leave with a musculoskeletal diagnosis as a homogeneous group. The results imply that rehabilitators should adopt a sensitive approach based on the sickness absentees’ wishes and views since the latter spend much of their time and thought during their period of sickness on counteracting distrust in search of an acceptable life role to regain respect.